Oxidative polymerization of aromatic amines: kinetic features and possible mechanisms. (December 2017) - Mezhuev, Yaroslav O.; Korshak, Yuri V.; Shtilman, Mikhail I.
Abstract : The state-of-the-art studies into the synthesis of electrically conducting polymers by oxidative polymerization of aromatic amines are surveyed. The attention is focused on polyaniline, the most important representative of this class of polymers. The concepts of possible mechanisms, types of active sites and kinetic features of the oxidative polymerization of aromatic amines are analyzed and integrated. Considerable attention is paid to the formation of the new phase having a catalytic action. Numerous effects reported in the literature are explained in terms of the views on oxidative polymerization of aromatic amines as a heterogeneous autocatalytic process. The bibliography includes 153 references.